KOMUNIKASI INTERPERSONAL AYAH PEKERJA DAN ANAK PEREMPUAN DALAM MENINGKATKAN KETERBUKAAN DIRI ANAK - Isabela Brenda Evelyne Fernando Putri Kalimau; Rina, Nofha (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
Communication within the family serves to foster a good relationship between parents and children, thus encouraging openness in children towards their parents. However, the role of a working father in society, focused on his job, limits the time available for communication with his children, hindering the child's openness towards their father. The role of the father, which significantly contributes to the development of his daughter, particularly during the early adulthood stage of 21-25 years old, a transitional period from adolescence to adulthood, has an impact. This study aims to determine how interpersonal communication between working fathers and their daughters can enhance the child's openness towards their father. The theory utilized in this research is interpersonal communication theory, focusing on the analysis of characteristics such as openness, empathy, support, positivity, and equality, as well as self-disclosure theory. The method employed in this study is descriptive qualitative research with an interpretative approach. The findings of this study indicate that interpersonal communication between working fathers and their adult daughters, aged 21-25 years old, possesses positive characteristics in terms of empathy, support, and positivity. However, there are still shortcomings in terms of openness and equality between them. To enhance the daughter's openness towards her father, improvements are still needed in terms of the dimension of time and the depth of conversation topics. Thus, it is necessary to enhance interpersonal communication so that the child can broaden their self-expression towards their working father. These conclusions are supported by data obtained through observation methods and in-depth interviews with key informants, resulting in detailed research findings. Expert informants also provided scientifically-based opinions to support the responses of the key informants and offered constructive suggestions regarding interpersonal communication between working fathers and their daughters to enhance the child's openness.